Problem solving : the basics (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. This lesson will help you master the art of tackling challenges with finesse. With real-life stories, expert insights, and case studies, we're here to help build effective problem-solving skills. From unravelling the essence of problem-solving to cultivating creativity and collaboration, this guide covers it all. Explore the problem-solving process - from identification to reflection - through engaging examples of how pioneers embraced innovation and learned from failures to how devastating disasters taught the world valuable lessons. Join us on this journey of empowerment, where understanding problems, thinking creatively, collaborating effectively, and embracing failure will redefine your approach to overcoming challenges. Learning Objectives Recognise the core principles of problem-solving Explore a systematic problem-solving process Establish how problem-solving requires creativity, collaboration and adaptability.